Sleep-Dependent Consolidation of Rewarded Behavior Is Diminished in Children with Attention Deficit Hyperactivity Disorder and a Comorbid Disorder of Social Behavior - Wiesner, Christian D.; Molzow, Ina; Prehn-Kristensen, Alexander; Baving, Lioba (Frontiers in Psychology, 2017)
Children suffering from attention-deficit hyperactivity disorder (ADHD) often also display impaired learning and memory. Previous research has documented aberrant reward processing in ADHD as well as impaired sleep-dependent consolidation of declarative memory. We investigated whether sleep also fosters the consolidation of behavior learned by probabilistic reward and whether ADHD patients with a comorbid disorder of social behavior show deficits in this memory domain, too. A group of 17 ADHD patients with comorbid disorders of social behavior aged 8-12 years and healthy controls matched for age, IQ, and handedness took part in the experiment. During the encoding task, children worked on a probabilistic learning task acquiring behavioral preferences for stimuli rewarded most often. After a 12-hr retention interval of either sleep at night or wakefulness during the day, a reversal task was presented where the contingencies were reversed. Consolidation of rewarded behavior is indicated by greater resistance to reversal learning. We found that healthy children consolidate rewarded behavior better during a night of sleep than during a day awake and that the sleep-dependent consolidation of rewarded behavior by trend correlates with non-REM sleep but not with REM sleep. In contrast, children with ADHD and comorbid disorders of social behavior do not show sleep-dependent consolidation of rewarded behavior. Moreover, their consolidation of rewarded behavior does not correlate with sleep. The results indicate that dysfunctional sleep in children suffering from ADHD and disorders of social behavior might be a crucial factor in the consolidation of behavior learned by reward.